Horrid Scenes and Marvellous Sights: The Citizen-Soldier and Sir Robert Ker Porter’s Spectacle of War - Ramsey, Neil (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThe period of the French Revolutionary and Napoleonic Wars is now widely viewed as seeing the emergence of the first modern or ‘total’ war, as whole populations came to be mobilised for the nation’s war effort. The period’s print culture and popular entertainments responded to these demands by creating a media spectacle, eliciting popular support for the war by enabling its audience to visualise scenes of conflict. Sir Robert Ker Porter’s work as both a writer and artist had a significant presence in this emergent spectacle of war. Utilising personal correspondence from eyewitnesses and placing enormous emphasis in his work on accurate depictions of warfare, he sought to enable the citizen to share the soldier’s view of war, allowing him or her to visualise and imagine conflict from the vantage point of the soldier and his subjective experience. Whilst Porter thus sought to provide images of willing sacrifice for the nation, there is nonetheless a transgressive aspect to his work. By privileging the soldiers’ personal view, the images presented by Porter could conflict with the state’s attempts to control information about the war. The articulation of a soldier’s subjective experience of war could be unsettling, eliciting affective and horrified responses to war that were far removed from the needs of a militaristic state.